Effects of Dietary Supplementation With Clostridium butyricum on Growth Performance, Apparent Digestibility, Blood Metabolites, Ruminal Fermentation and Bacterial Communities of Fattening Goats - Zhang, Chengrui; Yu, Qingyuan; Wang, Jihong; Yu, Yidong; Zhang, Yonggen; Sun, Yukun (Frontiers in Nutrition, 2022)
At present, Clostridium butyricum (C. butyricum) has been widely used to improve body health and produce monogastric animals. However, there are few reports on the effect and specific mechanism of action of Clostridium butyricum in ruminants. This study aimed to investigate the effects of Clostridium butyricum supplementation on growth performance and digestive microbiota of fattening goats. Twenty-four healthy Albas goats were randomly divided into 3 treatment groups with eight goats in each group. The treatments were: control group (CON) (basal diet, concentrate to forage ratio = 65:35); low-dose Clostridium butyricum (LCB) (basal diet plus 2.0 × 108 CFU/kg Clostridium butyricum); and high-dose Clostridium butyricum (HCB) (basal diet plus 1.0 × 109 CFU/kg Clostridium butyricum). The experiment lasted for 8 weeks after a 2-week adaptation period. Therefore, growth performance, rumen and rectum microbiota were evaluated in goats supplemented with Clostridium butyricum cooperating with its metabolites. The results showed that dietary supplementation with Clostridium butyricum significantly increased the pH (P < 0.05), but had no significant effect on growth performance (P > 0.05). Compared with the control group, dietary Clostridium butyricum supplementation significantly increased the relative abundance of Prevotella_1, ChristensenellaceAE_R-7_Group and PrevotellaceAE_UCG-003 (P < 0.05), and significantly decreased Succiniclasticum and Muribaculaceae_unclassified (P < 0.05). The relative abundance of Clostridium in the rumen was less than 1.0%. Moreover, 16S rDNA analysis showed that, fecal Clostridium or Clostridium butyricum count was significantly decreased (P < 0.05), and the relative abundance of Alistipes and Akkermansia were increased (P < 0.10) in the low-dose group compared with the control group. Supplementing Clostridium butyricum in a high-concentrate diet did not significantly affect the performance of goats, while regulation of the gastrointestinal microbiota and related metabolites was associated with rumen fermentation.